Back Cover: Resonance Raman Spectroscopy as a Tool to Monitor the Active Site of Hydrogenases (Angew. Chem. Int. Ed. 19/2013). Issue 19 (22nd April 2013) - Siebert, Elisabeth; Horch, Marius; Rippers, Yvonne; Fritsch, Johannes; Frielingsdorf, Stefan; Lenz, Oliver; Velazquez Escobar, Francisco; Siebert, Friedrich; Paasche, Lars; Kuhlmann, Uwe; Lendzian, Friedhelm; Mroginski, Maria‐Andrea; et al.
<x xml:space="preserve">Abstract</x> The biological conversion of hydrogen is catalyzed by [NiFe] hydrogenases utilizing a tailored bimetallic center. In their Communication on page 5162 ff. P. Hildebrandt, I. Zebger, M. Horch, and co‐workers use resonance Raman spectroscopy for the first time to characterize this active site by directly probing Fe–CO/CN vibrational modes. Applying an integrated spectroscopic and computational approach, this method provides new insights into structural and photochemical aspects of the [NiFe] site.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>